DEVELOPMENT AND SHAPING OF STUDENTS' INTRINSIC MOTIVATION IN PHYSICAL EDUCATION - Dragan Krivokapić; Olivera Krivokapić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The results of the recent studies concerning the impact of psychological factors on the school success show that, in average, only 50% of the success rate could be ascribed to developmental level of intelligence, while the remainder of the variable is saturated with factors of non-intellectual nature. Among the factors unconditioned by intellectual characteristics, the special role in motivation for effective studying is played by motivation for learning - especially the intrinsic one. It is understood that, when it comes to physical education, the intrinsic motivation sources are in fact primary sources, especially if we are striving to maintain motivation at the necessary level for a longer period. The process of development and maintenance of intrinsic motivation is of vital importance, particularly due to the fact that absenteeism or inactivity in physical education classes is becoming increasingly pronounced among students in higher grades of elementary and high schools. It should be borne in mind that the number of children spending most of their time in sitting position in front of their computers or TV sets is increasing on a daily basis. Consequently, we have higher incidence of postural deformities in elementary school-age children. Development and shaping of intrinsic motivation in terms of increasing willingness to do physical exercise systematically and continuously could be a means of diminishing the above-mentioned problems.